PENDAMPINGAN BELAJAR IPA BERBASIS SMART SOLUTION BAGI SISWA KELAS IX DI SMPN 3 TEPUS - ATUN ATUN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This learning assistance activity is based on the problems of class IX students who have difficulty solving UN questions, especially science. The purpose of this activity is to help class IX students in studying science material, especially solving problems using smart solutions. This activity is carried out using a learning mentoring method by a science teacher. The results of this learning mentoring activity, namely 1) increasing the understanding of class IX students in solving National Examination questions through quick and easy steps; 2) the students become more enthusiastic and enthusiastic in learning science material. This has a positive impact on students' interest in learning science which was initially considered a difficult subject. ABSTRAKKegiatan pendampingan belajar ini didasari oleh permasalahan para siswa kelas IX yang kesulitan dalam menyelesaikan soal-soal UN khususnya IPA. Tujuan kegiatan ini adalah untuk membantu siswa kelas IX dalam mempelajari materi IPA terutama penyelesaian soal-soal menggunakan smart solution. Kegiatan ini dilakukan dengan metode pendampingan belajar oleh guru IPA. Hasil kegiatan pendampingan belajar ini, yaitu 1) meningkatkan pemahaman siswa kelas IX dalam menyelesiakan soal-soal UN melalui langkah-langkah cepat dan mudah; 2) para siswa menjadi lebih bersemangat dan antusias dalam mempelajari materi IPA. Hal ini memberikan dampak yang positif terhadap ketertarikan siswa dalam belajar IPA yang pada awalnya dianggap sebagai mata pelajaran yang sulit.